Zero Plastic Campus: Fostering Vision and ‎Mission of Prophetic Values into The Behavior ‎of Campus Community - Saiful Hadi (State Islamic Institute of Madura, 2022)
One of the universal values ​​of Islamic education is to establish the human behavior of a learning - friendly environment, especially on campus, through efforts to maintain and keep an environment free from the plastic waste. One of the values is through designing prophetic values ​​on the existing